Epoxides and Aziridines from α,β-Unsaturated Aldehydes - V. Vchislo, Nadezhda (Mini-Reviews in Organic Chemistry, 2017)
Epoxides and aziridines are very useful small heterocycles. The synthesis of these threemembered heterocycles including those derived from α,β-unsaturated aldehydes is a dynamic area of research. Among numerous approaches to construction of three-membered cycles with O- or Nheteroatoms are metallo- and organocatalysis. This review summarizes and highlights the methods for the synthesis of epoxides and aziridines via transformations of α,β-enals, which have been developed over the last 10 years.
Keywords: asymmetric organocatalysis